Shared reading for enhancing receptive vocabulary in early second language education: A study of preschool children in a Polish-German bilingual program - Olpińska-Szkiełko, Magdalena; Patera, Mateusz (Neofilolog, 2025)
This paper focuses on the practice of shared reading of picture storybooks and its impact on the development of children’s second language (L2) skills, particularly receptive vocabulary. It presents findings from an empirical study conducted in a bilingual Polish-German kindergarten in Poznan, Poland, between 2017 and 2018. The primary objective of this study was to investigate to what extent learning processes occur during shared reading experiences in German as the second language and to identify the factors influencing learning outcomes. The study explored three variables: the duration of a child’s participation in the bilingual program, the congruence between visual illustrations and words forming the accompanying text, and the family’s linguistic background and language policy. The findings confirm that the impact of shared reading on fostering L2 development increases with the duration of a child’s participation in the bilingual program, indirectly highlighting the program’s effectiveness. Furthermore, children relied not only on illustrations, but also on verbal forms, to derive meaning, underscoring the importance of linguistic context in L2 learning. The family language factor had minimal influence on learning outcomes, indicating that shared reading benefits children regardless of the extent of German usage at home.